Women, Migration and Gendered Experiences - Danaj, Ermira (Springer Nature, 2022)
This open access book focuses on Albanian internal and international female migration and places gender at the heart of postsocialist transformation. It explores the vulnerabilities that arise for female citizens from the contradictory policies produced by the Albanian state. By illuminating the intersection of gender and migration, it shows how Albanian women are likely to embed themselves in complex social relations and migration trajectories. By focusing on various cases – internal, international, return, economic and student female migrants – the book underlines that migration does not follow any kind of evolutionary development, according to which women go from 'traditional’ to ‘modern' gender relations. By providing a compelling account on the complex negotiations and tactics women employ to deal with gender inequalities, this book leads to a better understanding of gender and migration entanglements. It is a useful read to students, academics in migration and gender studies as well as social scientists and policy-makers in European countries.